A Case of Adrenoleukodystrophy Presenting as Progressive Cerebellar Dysfunction - Seunguk Jung; Jong Won Chung; Ji Young Yun; Han-Joon Kim; Beom Seok Jeon (Journal of Movement Disorders, 2009)
X-linked adrenoleukodystrophy (X-ALD) is a hereditary neurological disorder affecting the nervous system and adrenal cortex. The phenotype of X-ALD ranges from the rapidly progressive cerebral form to milder adrenomyeloneuropathy. However, cerebellar manifestations are rare. We report a case of adrenoleukodystrophy presenting as progressive cerebellar dysfunction resembling olivopontocerebellar degeneration, with a review of the literature